Vertical carving glaze, simulated stone ceramic tile and preparation method of simulated stone ceramic tile

By using vertical carving glaze with specific chemical components and optimized preparation materials, the shortcomings of existing simulated stone tiles in surface texture and wear resistance are solved, and simulated stone tiles with high simulation, wear resistance and stain resistance are achieved.

CN119661081AActive Publication Date: 2025-03-21FOSHAN SANSHUI NEW PEARL CONSTR CERAMICS IND +2
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411851934.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-03-21
Estimated Expiration
2044-12-16

AI Technical Summary

Technical Problem

The existing simulated stone tiles have shortcomings in surface texture and wear resistance, and cannot meet the high requirements of kitchen and bathroom environments.

Method used

A vertical engraving glaze is used, with chemical components including Al2O3, SiO2, K2O, Na2O, CaO, MgO, SrO, BaO and ZnO. The light transmittance and crystal texture are improved by introducing zinc oxide and strontium oxide, and the texture clarity is improved by controlling the relative content of silica. At the same time, the calcium and magnesium content in the selected preparation raw materials are relatively high, forming a calcium-magnesium feldspar crystal phase, improving high-temperature fluidity and reaction activity.

Benefits of technology

It has achieved the ideal three-dimensional carving effect of simulated stone tiles, with delicate textures, high stone simulation, strong wear resistance, easy to remove surface stains, good anti-fouling effect, and is suitable for high-demand environments such as kitchens and bathrooms.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005190819250000091
    Figure BDA0005190819250000091
  • Figure BDA0005190819250000092
    Figure BDA0005190819250000092
  • Figure BDA0005190819250000101
    Figure BDA0005190819250000101
Patent Text Reader

Abstract

The invention discloses a vertical carving glaze, a simulated stone ceramic tile and a preparation method of the simulated stone ceramic tile, and belongs to the technical field of ceramics. According to the present invention, 18.12-20.15% of Al2O3, 250.14-53.51% of SiO2, 0.81-1.55% of K2O, 3.59-5.85% of Na2O, 6.32-8.28% of CaO, 3.82-5.65% of MgO, 3.16-5.45% of SrO, 1.12-2.36% of BaO and 3.86-5.45% of ZnO are adopted, and based on the special chemical composition, when the artificial stone ceramic tile is used for preparing the artificial stone ceramic tile, the ideal three-dimensional pattern carving effect is provided, the pattern is fine, and the stone simulation degree is high; meanwhile, the product is high in wear resistance, surface stains can be easily removed, and the antifouling effect is good.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ceramics, and in particular to a vertical sculpture glaze, simulated stone ceramic tile and a preparation method thereof. Background Art

[0002] Currently in the ceramic tile industry, soft-polished simulated stone ceramic tiles are very popular because of their warm surface texture and soft glaze. These products are generally prepared by using a surface glaze setting with a glossiness of about 30° and auxiliary fiber module treatment, or by post-polishing and waxing treatment. However, this type of simulated stone ceramic tile cannot achieve the delicate texture of traditional simulated stone ceramic tiles, and has the defects of being not scratch-resistant and not anti-fouling, and cannot be used in some kitchens and bathrooms that are easily scratched or dirty. Summary of the invention

[0003] Based on the defects of the prior art, the purpose of the present invention is to provide a three-dimensional carving glaze. Based on its special chemical composition, this product has an ideal three-dimensional carving effect when used in the preparation of simulated stone tiles, with fine texture and high stone simulation. At the same time, the product has high wear resistance, surface stains can be easily removed, and has a good anti-fouling effect.

[0004] In order to achieve the above object, the technical solution adopted by the present invention is:

[0005] A glaze for vertical sculpture, comprising the following chemical components in percentage by weight:

[0006] Al2O3 18.12~20.15%, SiO2 50.14~53.51%, K2O 0.81~1.55%, Na2O3.59~5.85%, CaO 6.32~8.28%, MgO 3.82~5.65%, SrO 3.16~5.45%, BaO1.12~2.36, ZnO3.86~5.45%, the balance is loss on ignition and some trace components.

[0007] Preferably, the glaze comprises the following raw materials in parts by weight:

[0008] 20-35 parts of albite, 5-10 parts of calcined kaolin, 4-8 parts of calcined zinc oxide, 5-10 parts of strontium carbonate, 3-10 parts of magnesium-containing frit, 3-6 parts of calcined alumina, 5-15 parts of calcium-containing frit, 10-20 parts of lithography frit, 5-15 parts of washed soil, 5-10 parts of burned talc and 3-7 parts of wollastonite.

[0009] Preferably, the sculpture frit comprises the following chemical components in percentage by mass: Al2O3 17.56-22.12%, SiO2 48.14-53.51%, K2O 0.51-1.55%, Na2O 2.89-4.35%, CaO 7.12-9.68%, MgO 2.82-4.15%, ZnO 2.86-4.45%, BaO 8.19-10.54%.

[0010] In the sculpture glaze described in the present invention, zinc oxide and strontium oxide are introduced as specific components for improving light transmittance and crystal texture, and the relative content of silicon dioxide is controlled, which can effectively improve the clarity of the surface texture and the coloring effect of the product. At the same time, due to the high content of magnesium oxide, calcium oxide and barium oxide, when applied to the preparation of ceramic tile firing, the solvent effect of the overall formula is good, the obtained glaze has higher transparency and good wear resistance, and the glaze can also take into account the anti-fouling effect after polishing.

[0011] When selecting raw materials for preparing freehand glaze, on the one hand, strontium carbonate is used as a sintering flux to lower the firing temperature of the entire material and optimize the high-temperature fluidity of the formula. Combined with a zinc source, the smoothness and fineness of the overall glaze can be improved. On the other hand, the calcium and magnesium content in the raw materials are set at a relatively high level, which allows these two elements to form calcium-magnesium feldspar crystal phases during the sintering process, further improving the fluidity and reactivity of the material in a high-temperature environment. In addition, the three types of frits can form tiny crystals during the sintering process, ensuring that the glaze is resistant to thermoplasticity during firing, and reducing problems such as pores and exhaust on the glaze, ultimately achieving a three-dimensional carving effect and significantly improving the anti-fouling effect.

[0012] Preferably, the calcium-containing frit comprises the following chemical components in percentage by mass: Al2O3 16.58-19.94%, SiO2 54.34-58.65%, K2O 1.65-2.56%, Na2O 2.35-3.58%, CaO 16.62-18.50%, and the remainder is loss on ignition and some trace components.

[0013] Preferably, the magnesium-containing frit comprises the following chemical components in percentage by mass: Al2O3 13.45-15.64%, SiO2 50.24-56.67%, K2O 2.14-3.15%, Na2O 3.85-5.35%, MgO 15.87-19.54%, and the remainder is loss on ignition and some trace components.

[0014] Preferably, the chemical composition of the glaze also includes 2-10% of loss on ignition and some trace components.

[0015] Another object of the present invention is to provide a simulated stone tile, comprising the vertical sculpture glaze of the present invention.

[0016] Preferably, the simulated stone tile comprises a body layer, a surface glaze layer, and a vertical sculpture glaze layer, and the vertical sculpture glaze layer comprises the vertical sculpture glaze described in the present invention.

[0017] Preferably, the surface glaze layer comprises the following chemical components in percentage by mass: Al2O3 22.56-26.12%, SiO2 56.14-62.51%, K2O 1.11-1.85%, Na2O 3.89-4.85%, CaO 0.32-1.88%, MgO 0.82-2.15%, ZrO2 4.86-7.5%, and the remainder is loss on ignition and some trace components.

[0018] Preferably, the surface glaze layer comprises the following raw materials in parts by weight: 6-12 parts of potassium feldspar, 8-15 parts of calcined kaolin, 30-40 parts of sodium feldspar, 5-15 parts of quartz, 8-15 parts of calcined alumina, 7-15 parts of zirconium silicate, 3-5 parts of burned talc, 1-5 parts of dolomite, and 8-12 parts of nepheline.

[0019] In order to cooperate with the sculptured glaze described in the present invention, when setting the surface glaze layer of the simulated stone tile, the introduction of zinc oxide can improve the compatibility of the glaze in the firing temperature range, and the compounding of calcined alumina and calcined kaolin can increase the initial melting temperature of the overall material, thereby avoiding the surface glaze layer from melting and closing too early during the firing process, thereby causing the gas to be discharged in time, thereby improving the density and fineness of the overall tile, and the product texture effect is better and the wear resistance is higher; in addition, zinc oxide can also increase the viscosity of the glaze after melting, so that the molten material can be filled into the gap in time after the exhaust on the surface of the material, thereby ultimately improving the product's anti-fouling effect, and there will be no situation where dirt and grime are hidden on the surface.

[0020] Preferably, the composition of the surface glaze layer also includes 2-10% loss on ignition and some trace components.

[0021] More preferably, the trace ingredients include zinc oxide and barium oxide.

[0022] Preferably, the simulated stone tile further comprises an inkjet printing layer arranged between the surface glaze layer and the vertical sculpture glaze layer.

[0023] By arranging an inkjet printing layer between the surface glaze layer and the vertical sculpture glaze layer on the simulated stone ceramic tile of the present invention, the simulated stone ceramic tile can utilize the principle of oily ink discharge during the firing process to make the formed simulated stone pattern clearer and more delicate, and even under specific patterns, it can present the unique spider web crack effect of natural stone, thereby significantly improving the ornamental value.

[0024] Another object of the present invention is to provide a method for preparing the simulated stone tile, comprising the following steps:

[0025] Setting a body layer;

[0026] Set the glaze layer;

[0027] Printing texture effect patterns on the glaze layer, setting the inkjet printing layer;

[0028] A vertical carving glaze layer is provided on the inkjet printing layer to obtain a rough blank;

[0029] The rough blank is fired and then polished to obtain the simulated stone tile.

[0030] During the preparation process of the simulated stone ceramic tile described in the present invention, an inkjet printing layer is pre-printed on the surface glaze layer with a texture pattern, and a vertical sculpture glaze layer is arranged on the layer. In this way, the physical ink discharge effect can be utilized during the firing process of the product to make the pattern present an ideal peeling effect, so that the upper and lower layers, especially the vertical sculpture glaze layer, are fully integrated with the pattern, and the stone texture and three-dimensional effect of the product are guaranteed to meet the expectations while achieving wear resistance and easy cleaning performance.

[0031] Preferably, the green body layer comprises the following raw materials in parts by weight:

[0032] 20-35 parts of potassium-sodium sand, 15-25 parts of ball clay, 10-15 parts of kaolin, 5-10 parts of bentonite, 4-10 parts of talc, 15-25 parts of potassium-sodium water abrasive, 3-5 parts of pyrophyllite, and 2-5 parts of diopside.

[0033] The preparation method of the green body layer is as follows: after ball milling and sieving the raw materials, the powder particles are transported to a press to be pressed into a green body, the green body is dried in a drying kiln at 140-160° C. for 40-60 minutes, and after the green body is taken out of the drying kiln, 20-30g / 2 of water to obtain the green body layer.

[0034] Preferably, the glaze layer is provided by applying glaze slurry;

[0035] More preferably, the preparation method of the glaze slurry is:

[0036] The raw materials for preparing each surface glaze layer are mixed, then water is added, mixed and ball-milled, and sieved to obtain the surface glaze slurry.

[0037] More preferably, the surface glaze slurry of the surface glaze layer slurry has a specific gravity of 1.88 to 1.92 g / mL and a water content of 28 to 32%.

[0038] More preferably, the glaze amount of the surface glaze layer is 400-500 g / m 2 .

[0039] Preferably, the glaze layer is provided by applying glaze slurry;

[0040] More preferably, the method for preparing the glaze slurry for vertical carving is:

[0041] The raw materials for preparing the glazes are mixed, and then water is added, mixed and ball-milled, and sieved to obtain an intermediate slurry with a specific gravity of 1.45-1.52 g / mL, and methyl water is added to mix to obtain a glaze slurry;

[0042] The mass ratio of the intermediate slurry to methyl water is (0.5-1.5):100.

[0043] More preferably, the glaze amount of the sculptured glaze layer is 400-500 g / m 2 .

[0044] Preferably, the inkjet printing layer is realized by printing pattern ink with a grayscale of 5 to 50%.

[0045] Preferably, the firing temperature is 1100-1200° C., and the firing time is 50-80 min.

[0046] The beneficial effect of the present invention is that the present invention provides a three-dimensional carving glaze, which, based on its special chemical composition, has an ideal three-dimensional carving effect when used in the preparation of simulated stone tiles, with fine texture and high stone simulation; at the same time, the product has high wear resistance, surface stains can be easily removed, and has a good anti-fouling effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figure 1 This is a schematic diagram comparing the simulated stone tile and stone described in Example 1 of the present invention.

[0048] Figure 2 This is a schematic diagram of the simulated stone tile after painting according to Example 1 of the present invention.

[0049] Figure 3 This is a schematic diagram of the simulated stone tile according to Example 1 of the present invention after being wiped with water after painting.

[0050] Figure 4 This is a schematic diagram of the simulated stone tile described in Comparative Example 5 of the present invention after being wiped with water after painting. DETAILED DESCRIPTION

[0051] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments and comparative examples, the purpose of which is to understand the content of the present invention in detail, rather than to limit the present invention. All other embodiments obtained by those of ordinary skill in the art without making creative work premise belong to the protection scope of the present invention. The experimental reagents and instruments involved in the implementation of the present invention, unless otherwise specified, are all commonly used common reagents and instruments.

[0052] Example 1

[0053] An embodiment of a vertical sculpture glaze, simulated stone tile and a preparation method thereof according to the present invention. The simulated stone tile comprises the following preparation steps:

[0054] (1) setting a green body layer;

[0055] The green body layer comprises the following raw materials in parts by weight:

[0056] 23 parts of potassium and sodium sand, 21 parts of ball clay, 12 parts of kaolin, 7 parts of bentonite, 5 parts of talc, 23 parts of potassium and sodium water abrasive, 3 parts of pyrophyllite, 3 parts of diopside, 3 parts of sodium sand;

[0057] After the raw materials are mixed and ball-milled, sieved and pressed, they are dried at 150°C for 50 min until the moisture content is less than 0.3% and the strength is above 1.8 MPa. Then, 25 g / m 2 of water wets the surface;

[0058] (2) applying glaze slurry on the green body layer through an electrostatic glaze spraying device to form a glaze layer;

[0059] The raw materials for preparing the surface glaze layer include the following components in parts by weight:

[0060] 8 parts of potassium feldspar, 12 parts of calcined kaolin, 37 parts of sodium feldspar, 10 parts of quartz, 8 parts of calcined alumina, 10 parts of zirconium silicate, 3 parts of calcined talc, 2 parts of dolomite, and 10 parts of nepheline;

[0061] The preparation method of the glaze slurry is:

[0062] The raw materials for preparing each glaze layer are mixed, then water is added and mixed and ball milled, and sieved through 325 mesh until the sieve residue is 0.7%, to obtain the glaze slurry. The specific gravity of the glaze slurry is 1.9g / mL, the water content is 30%, and the flow rate is 35s / 100mL; the glaze amount of the glaze layer is 450g / m 2 ;

[0063] The chemical composition of the glaze layer is shown in Table 1.

[0064] (3) Printing a texture effect pattern on the glaze layer and setting an inkjet printing layer;

[0065] (4) providing a vertical sculpture glaze layer on the inkjet printing layer to obtain a rough blank;

[0066] The glaze layer comprises the following raw materials in parts by weight:

[0067] 25 parts of albite, 6 parts of calcined kaolin, 4.5 parts of calcined zinc oxide, 5.5 parts of strontium carbonate, 5 parts of magnesium-containing frit, 3 parts of calcined alumina, 11 parts of calcium-containing frit, 18 parts of pedo frit, 5 parts of washed soil, 10 parts of burned talc and 7 parts of wollastonite;

[0068] The sculpture frit includes the following chemical components in percentage by mass: Al2O3 19.39%, SiO2 49.86%, K2O 0.86%, Na2O 3.54%, CaO 8.85%, MgO 3.19%, ZnO 3.6%, BaO 9.32%;

[0069] The calcium-containing frit includes the following chemical components in percentage by mass: Al2O3 16.62%, SiO2 58.01%, K2O 1.79%, Na2O 2.95%, CaO 17.31%;

[0070] The magnesium-containing frit includes the following chemical components in percentage by mass: Al2O3 14.50%, SiO2 55.36%, K2O 3.15%, Na2O 5.35%, and MgO 18.86%;

[0071] The chemical composition of the glaze layer is shown in Table 2.

[0072] The vertical sculpture glaze layer is achieved by applying vertical sculpture glaze slurry through an electrostatic glaze spraying device;

[0073] The preparation method of the vertical carving glaze slurry is:

[0074] The raw materials for preparing the glazes are mixed, and then water is added to mix and ball-milled, and sieved through 325 mesh to a sieve residue of 0.7% to obtain an intermediate slurry with a specific gravity of 1.48 g / mL, and methyl water is added to mix to obtain a glaze slurry;

[0075] The mass ratio of the intermediate slurry to methyl water is 1:100;

[0076] The glaze amount of the sculpture glaze layer is 450g / m 2 .

[0077] (5) The rough blank is fired at 1180° C. for 60 min, and then polished to obtain the simulated stone tile.

[0078] Example 2

[0079] An embodiment of a sculptured glaze, simulated stone tile and a preparation method thereof described in the present invention is different from Embodiment 1 in that the surface glaze layer comprises the following preparation raw materials in parts by weight: 8 parts of potassium feldspar, 12 parts of calcined kaolin, 30 parts of sodium feldspar, 12 parts of quartz, 10 parts of calcined alumina, 10 parts of zirconium silicate, 3 parts of burned talc, 5 parts of dolomite and 10 parts of nepheline.

[0080] Example 3

[0081] An embodiment of a sculptured glaze, simulated stone tile and a preparation method thereof described in the present invention is different from Embodiment 1 in that the surface glaze layer comprises the following preparation raw materials in parts by weight: 12 parts of potassium feldspar, 12 parts of calcined kaolin, 30 parts of sodium feldspar, 8 parts of quartz, 10 parts of calcined alumina, 11 parts of zirconium silicate, 5 parts of burned talc, 4 parts of dolomite and 8 parts of nepheline.

[0082] Example 4

[0083] An embodiment of a vertical sculpture glaze, simulated stone tile and a preparation method thereof according to the present invention is different from Embodiment 1 in that the vertical sculpture glaze layer comprises the following raw materials in parts by weight:

[0084] 22 parts of albite, 6 parts of calcined kaolin, 4 parts of calcined zinc oxide, 5 parts of strontium carbonate, 7 parts of magnesium-containing frit, 3 parts of calcined alumina, 10 parts of calcium-containing frit, 18 parts of lithography frit, 8 parts of washed soil, 12 parts of burned talc and 5 parts of wollastonite.

[0085] Example 5

[0086] An embodiment of a vertical sculpture glaze, simulated stone tile and a preparation method thereof according to the present invention is different from Embodiment 1 in that the vertical sculpture glaze layer comprises the following raw materials in parts by weight:

[0087] 25 parts of albite, 6 parts of calcined kaolin, 4 parts of calcined zinc oxide, 6 parts of strontium carbonate, 7 parts of magnesium-containing frit, 3 parts of calcined alumina, 12 parts of calcium-containing frit, 15 parts of lithography frit, 8 parts of washed soil, 9 parts of burned talc and 5 parts of wollastonite.

[0088] Comparative Example 1

[0089] A kind of vertical sculpture glaze and simulated stone ceramic tile prepared therefrom, which differs from Example 1 in that the surface glaze layer comprises the following preparation raw materials in parts by weight: 15 parts of potassium feldspar, 12 parts of calcined kaolin, 30 parts of sodium feldspar, 12 parts of quartz, 5 parts of calcined alumina, 10 parts of zirconium silicate, 3 parts of burned talc, 5 parts of dolomite and 8 parts of nepheline.

[0090] Comparative Example 2

[0091] A kind of vertical sculpture glaze and simulated stone ceramic tile prepared therefrom, which differs from Example 1 in that the surface glaze layer comprises the following preparation raw materials in parts by weight: 20 parts of potassium feldspar, 10 parts of calcined kaolin, 24 parts of sodium feldspar, 11 parts of quartz, 1 part of aluminum oxide, 10 parts of zirconium silicate, 8 parts of nepheline, 10 parts of air knife clay, 6 parts of calcite, and 5 parts of zinc oxide.

[0092] Comparative Example 3

[0093] A kind of vertical sculpture glaze and simulated stone tile prepared therefrom, which differs from Example 1 in that the surface glaze layer comprises the following preparation raw materials in parts by weight: 17 parts of potassium feldspar, 8-15 parts of calcined kaolin, 20 parts of sodium feldspar, 13 parts of quartz, 10 parts of calcined alumina, 9 parts of zirconium silicate, 13 parts of nepheline, 7 parts of air knife clay, 4 parts of barium carbonate, 4 parts of wollastonite, and 3 parts of calcined zinc oxide.

[0094] Comparative Example 4

[0095] A kind of vertical carving glaze and simulated stone ceramic tile prepared therefrom, which differs from Example 1 in that the vertical carving glaze layer comprises the following preparation raw materials in parts by weight: 40 parts of albite, 6 parts of calcined kaolin, 4 parts of calcined zinc oxide, 3 parts of strontium carbonate, 10 parts of dolomite, 8 parts of calcined alumina, 6 parts of wollastonite, 10 parts of vertical carving frit, 8 parts of washed soil, and 5 parts of burned talc.

[0096] Comparative Example 5

[0097] A vertical sculpture glaze and simulated stone tiles prepared therefrom, the difference from Example 1 being that the vertical sculpture glaze layer comprises the following raw materials in parts by weight: 37 parts of albite, 5 parts of calcined kaolin, 4.5 parts of calcined zinc oxide, 5.5 parts of strontium carbonate, 11 parts of dolomite, 3 parts of calcined alumina, 18 parts of frit, 5 parts of burned talc, 8 parts of washed clay and 3 parts of wollastonite;

[0098] The frit includes the following chemical components in percentage by mass: Al2O3 9.49%, SiO2 58.65%, K2O 8.04%, Na2O 0.54%, CaO 12.17%, and ZnO 9.59%.

[0099] Comparative Example 6

[0100] A kind of vertical sculpture glaze and simulated stone tile prepared therefrom, which differs from Example 1 in that the vertical sculpture glaze layer comprises the following preparation raw materials in parts by weight: 38 parts of albite, 9 parts of potassium feldspar, 6 parts of calcined kaolin, 5 parts of calcined zinc oxide, 6 parts of strontium carbonate, 8 parts of quartz, 3 parts of calcined alumina, 7 parts of washed soil, 5 parts of burned talc and 2 parts of wollastonite.

[0101] Comparative Example 7

[0102] A kind of vertical sculpture glaze and simulated stone tile prepared therefrom, which differs from Example 1 in that the vertical sculpture glaze layer comprises the following preparation raw materials in parts by weight: 33 parts of albite, 13 parts of potassium feldspar, 5 parts of calcined kaolin, 4 parts of calcined zinc oxide, 1 part of strontium carbonate, 10 parts of dolomite, 11 parts of quartz, 7 parts of calcined alumina, 11 parts of washed soil, 2 parts of burned talc and 3 parts of wollastonite.

[0103] Comparative Example 8

[0104] A kind of vertical sculpture glaze and simulated stone tile prepared therefrom, which differs from Example 1 in that the vertical sculpture glaze layer comprises the following preparation raw materials in parts by weight: 36 parts of albite, 6 parts of calcined kaolin, 4.5 parts of calcined zinc oxide, 5.5 parts of strontium carbonate, 10 parts of magnesium-containing frit, 6 parts of calcined alumina, 10 parts of calcium-containing frit, 12 parts of washed soil, and 10 parts of burned talc.

[0105] Comparative Example 9

[0106] A kind of vertical carving glaze and simulated stone ceramic tile prepared therefrom, which differs from Example 1 in that the vertical carving glaze layer comprises the following preparation raw materials in parts by weight: 35 parts of albite, 6 parts of calcined kaolin, 5 parts of calcined zinc oxide, 3 parts of strontium carbonate, 10 parts of magnesium-containing frit, 3 parts of calcined alumina, 11 parts of vertical carving frit, 12 parts of washed soil, 10 parts of burned talc and 5 parts of wollastonite.

[0107] Comparative Example 10

[0108] A vertical sculpture glaze and simulated stone tile prepared therefrom, the difference from Example 1 is that the vertical sculpture glaze layer comprises the following raw materials in parts by weight:

[0109] 20 parts of albite, 6 parts of calcined kaolin, 4.5 parts of calcined zinc oxide, 5.5 parts of strontium carbonate, 5 parts of magnesium-containing frit, 3 parts of calcined alumina, 6 parts of calcium-containing frit, 28 parts of diao frit, 5 parts of washed soil, 10 parts of burned talc and 7 parts of wollastonite; the diao frit comprises the following chemical components in mass percentage: Al2O3 14.35%, SiO2 45.62%, K2O 1.55%, Na2O4.56%, CaO 9.68%, MgO6.15%, ZnO 5.21% and BaO 9.12%.

[0110] Table 1

[0111]

[0112] Table 2

[0113]

[0114]

[0115] Effect Example 1

[0116] In order to verify the various properties of the simulated stone tiles of the present invention, the tiles prepared in the embodiments and comparative examples were subjected to the following tests:

[0117] (1) Texture evaluation test: 10 testers were selected to evaluate the surface texture of the product using the printed pattern as the control. The score ranged from 1 to 10 (integer points). The clearer and more realistic the texture, the higher the score, while the rougher and less realistic the texture, the lower the score. The average score of each sample was calculated and recorded.

[0118] (2) Antifouling performance test: The antifouling grade test was conducted in accordance with GB / T 3810.14-2016. The test used green pollutant chrome green in light oil, red pollutant in light oil, iodine solution, and olive oil as pollutants. The lowest grade among the test results of each pollutant was used for statistics.

[0119] (3) Cleanability test: Use blue ink for anti-fouling test, purple-blue ink, blue and black oil-based markers to draw pictures and lines on the surface of the tile within a range of 100X100mm. Then leave it for 24 hours, wet it with a sponge and rinse it with tap water for 3 minutes, then wipe it with a towel to observe whether the traces left after wiping are obvious and how easy it is to wipe.

[0120] (4) Wear resistance test: According to GB / T 3810.14-2016 Part 7 Determination of surface wear resistance of glazed tiles, the test sample is 100×100 mm, and 8 different sample positions are sampled for each embodiment or comparative example, and the test results are comprehensively judged.

[0121] The test results are shown in Table 3.

[0122] Table 4

[0123]

[0124]

[0125] It can be seen from the results that the simulated stone tiles provided with a specific surface glaze layer and a vertical sculpture glaze layer according to the present invention have good comprehensive performance, not only the simulated stone texture is clear and realistic, such as Figure 1 As shown, when the product obtained in Example 1 is compared with the sampled marble material, there is almost no apparent difference, and the grain evaluation also reaches at least 8.5 points. This is mainly due to the introduction of zinc and strontium in the vertical carving glaze during the setting, and the adjustment of the calcium, magnesium and barium contents, so that the glaze layer after firing is transparent. After the inkjet printing layer is set, the surface glaze layer with specific ingredients can fully exhaust and promote interlayer bonding during firing, and the principle of oily ink discharge is used to make the grain effect clear and delicate; in addition, such a design can also effectively improve the wear resistance and anti-fouling effect of the product. The anti-fouling grade of the products in each embodiment under the national standard test is 5, and the wear resistance test results reach 6000 revolutions and 4, which can be fully applied to working environments such as kitchens and bathrooms that have extremely high requirements for wear resistance and anti-fouling. In addition, the product is also easy to clean, such as Figure 2 and3 As shown, after the product of Example 1 is painted, the stains can be completely removed by simply wiping with water, and the product is highly convenient to use.

[0126] In contrast, the products described in Comparative Examples 1 to 3 have improper selection of raw materials when setting the surface glaze layer, resulting in improper chemical composition of the products, which not only reduces the texture effect, but also has poor anti-fouling and wear resistance. In the products of Comparative Examples 4 to 10, due to improper setting of the vertical sculpture glaze layer, some products have a texture score of only 6 points or less, and the lowest anti-fouling level is only level 3, and the cleaning difficulty is also increased. Figure 4 As shown, the product of comparative example 5 still has certain traces after cleaning, and the wear resistance test result of the product is only level 3 at 1500 revolutions.

[0127] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A vertical sculpture glaze, characterized in that: Includes the following chemical compositions in percentage by mass; Al2O3 18.12~20.15%, SiO2 50.14~53.51%, K2O 0.81~1.55%, Na2O3.59~5.85%, CaO 6.32~8.28%, MgO 3.82~5.65%, SrO 3.16~5.45%, BaO1.12~2.36, ZnO 3.86~5.45%.

2. The sculptured glaze according to claim 1, characterized in that: The preparation comprises the following raw materials in parts by weight: 20-35 parts of albite, 5-10 parts of calcined kaolin, 4-8 parts of calcined zinc oxide, 5-10 parts of strontium carbonate, 3-10 parts of magnesium-containing frit, 3-6 parts of calcined alumina, 5-15 parts of calcium-containing frit, 10-20 parts of lithography frit, 5-15 parts of washed soil, 5-10 parts of burned talc and 3-7 parts of wollastonite.

3. The sculptured glaze according to claim 2, characterized in that: The sculpture frit comprises the following chemical components in percentage by mass: Al2O3 17.56-22.12%, SiO2 48.14-53.51%, K2O 0.51-1.55%, Na2O 2.89-4.35%, CaO 7.12-9.68%, MgO 2.82-4.15%, ZnO 2.86-4.45%, BaO 8.19-10.54%, and the remainder is loss on ignition and some trace components.

4. The sculptured glaze according to claim 2, characterized in that: The calcium-containing frit comprises the following chemical components in percentage by mass: Al2O3 16.58-19.94%, SiO2 54.34-58.65%, K2O 1.65-2.56%, Na2O 2.35-3.58%, CaO 16.62-18.50%, and the remainder is loss on ignition and some trace components.

5. The sculptured glaze according to claim 2, characterized in that: The magnesium-containing molten block comprises the following chemical components in percentage by mass: Al2O3 13.45-15.64%, SiO2 50.24-56.67%, K2O2.14-3.15%, Na2O 3.85-5.35%, MgO 15.87-19.54%, and the remainder is loss on ignition and some trace components.

6. A simulated stone tile, characterized in that: It includes the sculptured glaze as described in any one of claims 1 to 5.

7. The simulated stone tile according to claim 6, characterized in that: The simulated stone tile includes a body layer, a surface glaze layer, and a vertical sculpture glaze layer, and the vertical sculpture glaze layer includes the vertical sculpture glaze; the surface glaze layer includes the following chemical components in mass percentage: Al2O3 22.56-26.12%, SiO2 56.14-62.51%, K2O1.11-1.85%, Na2O 3.89-4.85%, CaO0.32-1.88%, MgO 0.82-2.15%, ZrO24.86-7.5%, and the remainder is loss on ignition and some trace components.

8. The simulated stone tile according to claim 7, characterized in that: The surface glaze layer comprises the following raw materials in parts by weight: 6-12 parts of potassium feldspar, 8-15 parts of calcined kaolin, 30-40 parts of sodium feldspar, 5-15 parts of quartz, 8-15 parts of calcined alumina, 7-15 parts of zirconium silicate, 3-5 parts of calcined talc, 1-5 parts of dolomite, and 8-12 parts of nepheline.

9. The simulated stone tile according to claim 6, characterized in that: The simulated stone tile also includes an inkjet printing layer arranged between the surface glaze layer and the vertical sculpture glaze layer.

10. The method for preparing the simulated stone tile according to any one of claims 6 to 9, characterized in that: The following steps are involved: Setting a body layer; Set the glaze layer; Printing texture effect patterns on the glaze layer, setting the inkjet printing layer; A vertical carving glaze layer is provided on the inkjet printing layer to obtain a rough blank; The rough blank is fired and then polished to obtain the simulated stone tile.

Citation Information

Patent Citations

  • Simulation micro-cement ceramic tile and preparation method thereof

    CN115180982A

  • Raw stone glaze, raw stone ceramic tile and preparation method thereof

    CN115231826A

  • Antique glazed tile and preparation method thereof

    CN116177985A

  • Glaze with silk glaze texture and ceramic tile

    CN117003488A